Digitalisasi Keuangan UMKM : Pelatihan Pembuatan Laporan Keuangan Praktis dengan Microsoft Excel untuk Daya Saing yang Lebih Baik - Wulandari, Ika; Zaman, Delfian; Kurniawan, Mohd. Ideal; Hanimah, Nur (Ikatan Cendekiawan Muda Akuntansi, 2024)
One of the tri dharma obligations of lecturers is to carry out Community Service (PKM) activities. The PKM activity carried out this time by the LP3I Pekanbaru Polytechnic PKM Team for the Accounting Computerization Study Program was Digitalization of MSME finances, namely providing training in making practical financial reports using Microsoft Excel to 15 MSMEs who are members of the Bertuah MSME Community in the city of Pekanbaru. The aim of holding this training is so that in this digital era, all MSMEs must also develop to keep up with the times, one of which is making MSME financial reports no longer manual, at least MSME financial reports already use computerization in the form of Microsoft Excel. By using Microsoft Excel, it is hoped that all MSMEs will have recorded financial reports, which can be made faster and save time compared to manually. Apart from that, MSME owners can also see the condition of their business from the financial reports prepared. Apart from that, what is no less important is that with financial reports, MSMEs will easily report taxes and can use them to apply for credit/loan funds to banks. if you want to increase capital for MSMEs so that they can develop further. Keywords: MSMEs, Financial Digitalization, Microsoft Excel, Financial Reports